ANKYLOGLOSSIA AND BREASTFEEDING PROBLEMS - Andreja Valcl (The Society for Children with Metabolic Disorders, 2022)
Ankyloglossia (tongue-tie) is a congenital oral anomaly characterised by a short lingual frenulum, which may restrict tongue mobility and therefore cause breastfeeding problems. The definition of ankyloglossia is not standardised, and there are varying opinions regarding its clinical significance and optimal management. It occurs in approximately 0.1% to 12.1% of infants. There is evidence that this condition can cause feeding, swallowing and speech problems. The World Health Organisation recommends exclusive breastfeeding for the first six months of life. Their statement places more responsibility on healthcare workers to identify infants with potential breastfeeding problems. Between 25% and 44% of infants with ankyloglossia experience breastfeeding problems. The initial intervention for mothers breastfeeding infants with tongue-tie is lactation consultation. If breast-feeding problems continue, a procedure called frenulotomy is performed to release the frenulum.